SISTEM INFORMASI PENJUALAN SPAREPART MOBIL BERBASIS WEB PADA CV.CIPTA MANDIRI JAYA - Wijaya, Vivi; Nababan, Marlince Novita Karoseri (Sisfokomtek, 2020)
The spare parts that are currently running are less efficient because during the process of selling and recording the spareparts that require a long time, the management of the unbalanced company that is taking place in Cipta Mandiri Jaya is one of thecompanies that sell car parts. The existence of a debate, then we need an information system that can help smooth operational processes.The purpose of designing this system is to provide the required report information quickly for CV. Cipta Mandiri Jaya. Informationsystems for sales of goods are designed using the PHP programming language and MySQL as the database. The application that canreduce and minimize the problem of counting, makes it easier to make purchases, sales and purchase transactions more effectively andefficiently and is supported by a high level of data security